A One Health Evaluation of the Southern African Centre for Infectious Disease Surveillance - Hanin, Marie C. E.; Queenan, Kevin; Savic, Sara; Karimuribo, Esron; Rüegg, Simon R.; Häsler, Barbara (Frontiers in Veterinary Science, 2018)
Rooted in the recognition that emerging infectious diseases occur at the interface of human, animal and ecosystem health, the Southern African Centre for Infectious Diseases Surveillance (SACIDS) initiative aims to promote a trans-sectoral approach to address better infectious disease risk management in five countries of the Southern African Development Community. Nine years after SACIDS’ inception, this study aimed to evaluate the programme by applying a One Health (OH) evaluation framework developed by the Network for Evaluation of One Health (NEOH). The evaluation included a description of the context and the initiative, illustration of the theory of change, identification of outputs and outcomes, and assessment of the OHness. The latter is the sum of characteristics that defines an integrated approach and includes OH thinking, OH planning, OH working, sharing infrastructure, learning infrastructure, and systemic organisation. The protocols made available by NEOH were used to develop data collection protocols and identify the study design. The framework relies on a mixed methods approach by combining a descriptive and qualitative assessment with a semi-quantitative evaluation (scoring). Data for the analysis were gathered during a document review, in group and individual interviews and in an online survey. Operational aspects (i.e. OH thinking, planning, and working) were found to be balanced overall with the highest score in the planning dimension, whereas the infrastructure (learning infrastructures, systemic organisation, and sharing infrastructure) was high for the first two dimensions, but low for sharing. The One Health Index calculated was 0.359 and the One Health Ratio was 1.495. The programme was praised for its great innovative energy in a difficult landscape dominated by poor infrastructure and its ability to create awareness for OH and enthuse people for the concept; training of people and networking. Shortcomings were identified regarding the balance of contributions, funds and activities across member countries in the South, lack of data sharing, unequal allocation of resources, top-down management structures and limited horizontal collaboration. Despite these challenges, SACIDS is perceived to be an effective agent in tackling infectious diseases in an integrated manner.